Gonocephalus doriae (Marquis Doria’s Angle-headed Lizard) - Mhhammad Aini, Ujang; Hadimar, .; Sánchez, K.L.; Maiwald, M.J.; Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2021)
A new record of the agamid lizard Gonocephalus doriae from Kalimantan Barat is presented